Strengthening Environmental Law Policy and Its Influence on Environmental Sustainability Performance: Empirical Studies of Green Constitution in Adopting Countries - Suryawan, I. Gusti Bagus; Aris, Ismail (International Journal of Energy Economics and Policy, 2020)
Constitutional provisions concerning environmental protection have not specifically been regulated as expressive verbis in the Indonesian Constitution. In fact, the position of the environment has not been seated as a legal subject, and there is an absence of constitutional obligations for central government and local government and corporations and citizens, to protect the environment as a legal subject. Although Indonesia is very rich in natural resources, there are no provisions for constitutional procedures, such as constitutional complaint or suite action, and constitutional questions, to carry out environmental protection and the protection of environmental rights in constitutional courts or the supreme court. This study aims to explore the commitment of the State in its supreme law of constitution to carry out eco-constitutional reform agenda as the supreme action of the law to realize the ecocracy constitution as the new paradigm of environmental sovereignty. The results show that some countries have strengthened the position of living environments as a legal subject and placed it in their constitutions. However, if compared to the constitution of other countries, Indonesia’s current constitution is very far behind the idea of eco-constitutionalism or ecocracy, such as the constitutions of Ecuador, Bolivia, Switzerland, Egypt, and France which explicitly supports the environment, like water, mountains, sea, rivers, forests, animals, as subjects of law and the State, corporation, and citizens are obliged to protect them. Keywords: natural resources policy, ecocracy, eco-constitutionalism constitutional design, environmental protection. JEL Classifications: K32, Q56 DOI: https://doi.org/10.32479/ijeep.8719